Chitosan-modified fly-ash/kaolin ceramic membrane for enhancing FOG-water separation performance - Eny Apriyanti; Heru Susanto; I Nyoman Widiasa (Dept. of Chemical Engineering, Diponegoro University, 2023)
Ceramic membranes with efficient construction can save costs and simplify the wastewater treatment process. The price of raw materials and the amount of energy used during the sintering process are the two key factors that affect the final cost of ceramic membranes. This work used kaolin and fly ash recovered from power plants as the support membrane and chitosan as selective layer of composite ceramic membranes. Rigid alumina particles were added to the supports to bring them into alignment with the sintering temperature of the fly-ash/kaolin support. Additionally, the chitosan layer coating increased the supports' bending strength. By simple surface coating, chitosan with different molecular weights was spread over the fly-ash/kaolin supports. The membranes' average pore size radius and porosity were 20 nm and 49%, respectively. The oil removal rate was over 99.8% and the stable permeance was close to 20.5 Lm2h1 when treating oil-water emulsions with 400 mg/L oil content. This is most likely because of the super-hydrophilic performance of kaolin and the electrostatic repulsion between the membrane and oil droplets. The fabricated membranes also demonstrated high antifouling performance by enhancing FRR up to 88% and reduced the reversible fouling ratio. This study suggests that modified membrane has great potential for practical application in oily wastewater treatment.